Toward a Comprehensive Tax Reform for Italy - Cammeraat, Emile; Crivelli, Ernesto (Washington, D.C. : International Monetary Fund, 2020)
This paper evaluates elements of a comprehensive reform of the Italian tax system. Reform options are guided by the principles of reducing complexity, broadening the tax base, and lowering marginal tax rates, especially the tax burden on labor income. The revenue and distributional implications of personal income and property tax reforms are assessed with EUROMOD, while a microsimulation model is developed to evaluate VAT reform options. Simulations suggest that a substantial reduction in the tax burden on labor income can be obtained with a revenue-neutral base-broadening reform that streamlines tax expenditures and updates the property valuation system. In addition, a comprehensive reform would benefit low- and middle-income households the most, by lowering significantly their overall current tax liability, which results in increased progressivity of the tax system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet